Analisis Wacana Kritis Theo Van Leeuwen (Mengangkat Isu Rasisme Terhadap Etnis Tionghoa di Media Sosial X) (International Forum of Researchers and Lecturers, 2024)
This research aims to reveal racism in a number of posts on X's social media regarding Chinese ethnicity. These posts were studied using Theo Van Leeuwen's qualitative critical discourse analysis approach. This approach will reveal the process of inclusion and exclusion in posts about Chinese ethnicity. This process shows the existence of racist attitudes towards this group. The data analyzed are uploads, comments and interactions related to Chinese ethnicity on the social media platform X. The data collection techniques used in this research are documentation techniques and note-taking techniques. This research concludes that the exclusion processes found were passivation and nominalization, while the inclusion processes found were objectivation, abstraction, nomination, determination, indetermination, assimilation, and association. Through this analysis, it was revealed that the discourse in the upload reflected the attitude of the account user towards ethnic Chinese through the upload that had been written.